Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) -supported inter-sectoral coordination leads to long-term climate-resilient agricultural strategy in Senegal - Jaquet, Stéphanie (2023)
AICCRA-supported activities led to changes in the Ministry of Environment, Sustainable Development and Ecological Transition (MEDDTE) and the Ministry of Agriculture, Rural Equipment and Food Sovereignty (MAERSA) climate planning processes. The ministries adopted a participatory approach, built a common understanding of climate challenges, and created a national dialogue on climate change. The country of Senegal launched the process of developing its long term, low carbon, climate resilient agricultural development pathway (Agriculture LTS) in May 2021. The process set to build on an existing long-term planning vision of the Senegalese climate agenda, which must be aligned to the National Determined Contribution (NDC).